2021
DOI: 10.3389/fonc.2021.730282
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Initial Treatment Response to Transarterial Chemoembolization in Intermediate-Stage Hepatocellular Carcinoma by the Integration of Radiomics and Deep Learning

Abstract: ObjectivesWe aimed to develop radiology-based models for the preoperative prediction of the initial treatment response to transarterial chemoembolization (TACE) in patients with hepatocellular carcinoma (HCC) since the integration of radiomics and deep learning (DL) has not been reported for TACE.MethodsThree hundred and ten intermediate-stage HCC patients who underwent TACE were recruited from three independent medical centers. Based on computed tomography (CT) images, recursive feature elimination (RFE) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…For example, multiple high-quality studies reached good performance in predicting outcome before transarterial chemoembolizations (TACE) in hepatocellular carcinoma (HCC). [83][84][85][86][87][88] Transarterial radioembolization (TARE) has been investigated less extensively compared to TACE. Only some pilot studies have suggested radiomics features might be associated with outcome after TARE for HCC, liver metastases and intrahepatic cholangiocarcinoma.…”
Section: Artificial Intelligence In Interventional Oncologymentioning
confidence: 99%
“…For example, multiple high-quality studies reached good performance in predicting outcome before transarterial chemoembolizations (TACE) in hepatocellular carcinoma (HCC). [83][84][85][86][87][88] Transarterial radioembolization (TARE) has been investigated less extensively compared to TACE. Only some pilot studies have suggested radiomics features might be associated with outcome after TARE for HCC, liver metastases and intrahepatic cholangiocarcinoma.…”
Section: Artificial Intelligence In Interventional Oncologymentioning
confidence: 99%
“…Its performance was assessed using confusion matrices and receiver operating characteristic curves, and the model attained an AUC over 0.90 for all four classes in both validation sets, and accuracies of 85.1% and 82.8% for validation sets 1 and 2, respectively. In the next year, they combined conventional radiomics and DL to build a new CECT-based DLR model that served to predict the initial treatment response to TACE of HCC patients preoperatively[ 46 ]. Different from their prior work, they designed their own CNN for feature extraction and prediction, and the DL model was integrated with five radiomics models built with different classic machine learning algorithms or tumor size feature to build integrated models for efficacy comparison.…”
Section: Dlrs For Liver Cancermentioning
confidence: 99%
“…Although some PET and MRI based radiomics studies have achieved remarkable results in the field of metastatic colorectal cancer ( 12 , 13 ), CT based imaging criteria are still the preferred criteria for evaluation of tumor drug response in clinical trials so far. CT-based radiomics has been shown to help predict therapy response and outcome in multiple cancers, including CRC ( 14 16 ). Ligero et al.…”
Section: Introductionmentioning
confidence: 99%